Adaptive Robust Motion Control for Linear Induction Motor with Electromagnetic Nonlinearity Compensation. Issue 5 (24th July 2018) - Lu, Linlin; Sun, Peng; Xu, Linsen; Luo, Minzhou
Abstract: This paper presents an adaptive robust motion control algorithm for linear induction motor (LIM) with electromagnetic nonlinearity compensation to suppress nonlinear magnetic thrust reduction due to the end effect. The electromagnetic compensation adaptive robust control (ECARC) algorithm is developed to deal with the parametric uncertainties and uncertain nonlinearities that are widely present in LIM. This algorithm employs a discontinuous projection‐type method to estimate the system parameters. The disturbance is bounded by a critical value, which guarantees that the system is exponentially stable. However, due to the magnetic field distortion caused by the opening of primary ends, the relationship between the driving current and the resultant motor thrust is nonlinear. Consequently, electromagnetic thrust and flux are calculated and used for feedback compensation. Different from the traditional vector control and direct torque control, the control algorithm employs electromagnetic thrust and magnetic flux to compensate torque current and magnetic field. Simulation results and comparative experimental results show that current control algorithm is accurate and efficient.